Odpowiedzi

Najlepsza Odpowiedź!
2010-03-28T18:31:51+02:00
X+2y-4-3+y=x+3y-7
x+2y-4-2y-4x-5=-3x-9
-7+3y-3+y=4y-10
-7+3y-2y-4x-5=-4x+y-12
3y-4+1/2x-2y-3+y=1/2x+2y-7
3y-4+1/2x-2y-4x-5=-3 1/2x +y-9


a)(a+b)+[-(6-a)+b)=a+b-6+a+b=2a+2b-6
b)(a+b+c) - [a+(a-b-c)]=a+b+c-a-a+b+c=-a+2b+2c
c)x+[-(y+x)+x-(y-1)]=x-y-x+x-y+1=x-2y+1
2010-03-28T18:40:57+02:00
X+2y-4 - 3+y = x+3y - 7
x+2y-4 - 2y-4x -5 = -3x-4
-7+3y - 3+y = 4 y -10
-7+3y - 2y-4x-5= - 4x + y -12
3y - 4 + 1/2x - 3+y = 1/2 x +4y -7
3y - 4 + 1/2x - 2y-4x -5 = - 3 1/2 x +y -9